Land snails and slugs of Marai Parai area, western part of mount Kinabalu, Kinabalu Park, Sabah - Liew, Thor Seng; Florina Anthony; Lanting Lumkin; Scholastica Lanting (Sabah Parks Nature Journal, 2024)
Mount Kinabalu is a renowned biodiversity hotspot for land snails, with numerous species documented since the 19th century. Despite extensive studies, significant portions of the mountain, particularly the western and northern areas, remain unexplored. Twenty-six species of land snails and slugs were recorded in seven-day sampling along at the standard sampling plots and random locations along the two trails ascending to the Marai-Parai area, between 1000 m and 2500 meters above sea level at the western part of Mount Kinabalu, Sabah. While no new species were identified, our findings contribute to the taxonomic understanding of Vitrinula and Microparmarion species. Notably, we rediscovered Microparmarion pollonerai and observed novel behaviours of Microparmarion species in association with Nepenthes plants.